Key factors of success in the application of last planner system in construction work - Mandala, Andrean; Widyaningsih, Nunung; Purwoko Kusumo Bintoro, Bambang (International Journal of Engineering and Technology, 2020)
This study aims to identify what factors are the key to the successful implementation of the Last Planner System in construction work based on existing journals to be applied in the construction environment and determine the priority weight / key factors of success from the questionnaire results from experts with the Analytic method Hierarchy Process. The method used in this study uses the Analytic Hierarchy Process to find priority weights and software uses Expert Choice. From the results of the analysis obtained Key Success Factors in construction work, namely as many as 10 criteria where stakeholder criteria with the highest priority weight with a global weight of 0.2279 which have a value of consistency ratio below 0.1 or 10%, ie 0.08 or 8%, then an evaluation of the comparison pairing between criteria is consistent and as many as 24 sub-criteria where the sub-criteria of stakeholder support for the implementation of LPS with the highest priority weighting with a global weight of 0.1812 which has a consistency ratio below 0.1 or 10% ie 0.07 or 7%, then an assessment of pairwise comparisons between sub criteria are consistent.Â Â